Notch signaling, hypoxia, and cancer - Guo, Mingzhou; Niu, Yang; Xie, Min; Liu, Xiansheng; Li, Xiaochen (Frontiers in Oncology, 2023)
Notch signaling is involved in cell fate determination and deregulated in human solid tumors. Hypoxia is an important feature in many solid tumors, which activates hypoxia-induced factors (HIFs) and their downstream targets to promote tumorigenesis and cancer development. Recently, HIFs have been shown to trigger the Notch signaling pathway in a variety of organisms and tissues. In this review, we focus on the pro- and anti-tumorigenic functions of Notch signaling and discuss the crosstalk between Notch signaling and cellular hypoxic response in cancer pathogenesis, including epithelia-mesenchymal-transition, angiogenesis, and the maintenance of cancer stem cells. The pharmacological strategies targeting Notch signaling and hypoxia in cancer are also discussed in this review.